Multipolarity After Ukraine Old Wine in New Bottles? - Ferrari, Aldo (ISPI Publications, 2023)
One year after the full-scale invasion of Ukraine, the war has exacerbated the rift between Russia and the "collective West". While Western governments have been steadfast in punishing Russia for the invasion, other countries around the world have been more ambiguous, at times even choosing to side with Moscow politically or economically. These dynamics have revived the idea of a shift towards multipolarity along an anti-Western trajectory. Are we really heading in that direction? Are we facing increasing fragmentation due to the war or a re-consolidation of longstanding alliances? What principles underlie the formation of these blocs? What are the consequences of these dynamics for global security and the global economy? This Report aims to shed light on these questions, while also outlining the war's possible future implications for the Russian Federation, the "West", and the international order.